Parceria escola e família: a importância da família no processo ensino-aprendizagem da criança - PANTOJA, Doralice da Costa (2019)
The relationship between the school and the student's family still has many myths. There is often opposition to ideas, even if both have a common goal: the full development of children. The research was carried out at the Municipal School of Infantile Education São João, in the municipality of Abaetetuba / Pará. Thus, the present work aims to understand the importance of the relationship between the family and the school so that the child has a full development in the learning process aiming at an effective education. For the theoretical basis, we will use some authors such as Goldemberg, Triviños, Giddens, the Statute of the Child and the Adolescent (ECA), in particular, the theories of Vygotsky and Piaget, to better understand the discussion concerning the theme of the work. The subjects participating in this research were teachers, parents of students, students and pedagogical coordination. To do so, this work is organized in three parts, the first one regarding the concepts of learning, addressing the studies of Piaget and Vygotsky, as well as the functions that the school and the family represent in the learning process. The second part discusses the importance of the family in the formation of the child, emphasizing the process of family participation in school, emphasizing the importance of the school council as a mediator in the relationship between family and school. The third part is in charge of research, application of procedures for data collection, analysis of data and results obtained. This research led us to conclude that in the dynamism of school practices, teachers are historical agents, professionals with a great social responsibility, who must constantly be in search of continuous formation, as real researchers and scholars, which should contribute to strengthen participation of the family in the educational process of the students.